Blue Helmet Havens: Peacekeeping as Bypassing in Liberia and the Democratic Republic of the Congo. Issue 2 (14th March 2016) - Jennings, Kathleen M.
ABSTRACT: It is commonly argued that international peace interventions will work better and more empathetically if the prevailing separation between international interveners and local people is lessened. However, I argue that, outside the microeconomic interactions and transactional relationships that comprise the peacekeeping economy, peacekeeping is characterized by bypassing – intentional circumvention – or simple exclusion of the local. Drawing on fieldwork in Liberia and the Democratic Republic of the Congo, I argue that the rules and regulations, norms and architecture of UN peacekeeping all favour and are actively disposed to bypass or exclude. Accordingly, insofar as lessening the separation between internationals and locals is necessary to enable more effective and, ideally, empathetic peacekeeping, what is needed is systemic change that runs counter to the – mostly deliberate – policies that have been enacted to effectuate and retain this very separation over the past decade or more. The likelihood of such change is small.